Assessment of Napier grass accessions in lowland and highland tropical environments in east Africa: productivity and forage quality - Mwendia, Solomon W.; Yunusa, I.A.M.; Sindel, B.M.; Whalley, D.B.; Kariuki, I.W. (Cambridge University Press, 2017)
Ten accessions of Napier grass (Pennisetum purpureum Schumach.) were evaluated for their dry matter (DM) yield and forage quality in a semi-arid lowland (Katumani) and a relatively wet highland (Muguga) over seven growth cycles from 2011 to 2013 in tropical Kenya. Three biomass yield clusters were identified from the 10 accessions as high-yielding (HYC), medium-yielding (MYC) and low-yielding (LYC) clusters for both sites. Total biomass (shoot and root) yields (t ha−1) over the seven growth cycles were 25.3 for HYC, 22.2 for MYC and 19.6 for LYC at Katumani and 40.0, 41.4 and 29.1 at Muguga. Total biomass yield averaged over the study period was DM 22.4 t ha−1 at Katumani and 36.8 at Muguga. Rainfall productivity was higher at Katumani (28.8 kg ha−1 mm−1) than 20.8 kg ha−1 mm−1 at Muguga. Neutral detergent fibre (NDF) was lower in LYC, which was more leafy than the other clusters and there was little difference in NDF between the two sites.